To evaluate the anti-diabetic effects of Salvia cabulica ethanolic extract on alloxan-induced diabetic rabbits - Abdul Ghaffar; Marvi; Mohammad Younis; Abdul Wahid; Shafi Muhammad; Faisal Ahmed (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2022)
Objective: This study aimed to investigate the hypoglycemic effects of Salvia cabulica ethanolic extract on alloxan-induced diabetic rabbits.  Method: During the plant's extraction, the dried plant was soaked in ethanol for 14 days at room temperature and filtered. The dark green gummy filtrate was obtained by using a rotary evaporator at 40oC. Rabbits with fasting glucose levels of more than 250 mg/dL were considered diabetic. These rabbits were treated with aqueous plant extract in different doses (250 mg and 500 mg) respectively.  Results: The fasting blood glucose level (BGL) mean was 293 ± 25.65 in diabetic control group D-I compared to the normal control group A 99 ± 6.16 after the 48 hours of diabetes induction. The fasting blood glucose level (BGL) in group D-II was 192 ± 17.06, group D-III 93.515.95and group D-IV was 89.33 ± 7.79.  There was a significant decrease in blood glucose among the group III and IV treated with plant extract at 250 mg/kg and 500 mg/kg, respectively Conclusion: The plant Salvia cabulica has potential hypoglycemic activity. Therefore, the medicinal plant can be used as a folklore herbal drug in the treatment of diabetes locally.